MILESTONE-BASED FUNDING DALAM VENTURE CAPITAL: ANALISIS KRITIS DISTRIBUSI RISIKO PERSPEKTIF ABU HANIFAH - Hilwa Shabira; Muhammad Maulana (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
Startup developments have driven the rise of modern financing models such as venture capital through milestone-based funding mechanisms. While this staged scheme effectively mitigates investment uncertainty, it raises concerns regarding unfair risk distribution (risk shifting). Investors retain the flexibility to halt funding when targets are missed, whereas entrepreneurs bear the loss of expended resources. This study aims to analyze risk distribution in milestone-based funding and evaluate its alignment with Abu Hanifah’s thought on contractual justice. Using a qualitative-descriptive method, the findings reveal that although this scheme enhances financing efficiency, its implementation does not fully align with Abu Hanifah’s principle of al-ghunm bi al-ghurm (the balance of return and risk), as it tends to shift the risk burden unilaterally. Consequently, this study proposes a financing model reconstruction by restricting unilateral termination, implementing shared downside risk, and integrating musyarakah principles to foster a fairer and more balanced venture capital ecosystem.